2021
DOI: 10.33963/kp.a2021.0113
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between left atrial strain and left atrial pressures values in patients undergoing atrial fibrillation ablation

Abstract: Background:We aimed to investigate the correlations between left atrial strain (LAS) assessed by speckle tracking echocardiography and directly measured left atrial pressures (LAP) values and to estimate the features of patients with lower LAS values. Methods:A prospective, observational study was performed on patients with atrial fibrillation (AF) undergoing ablation. Detailed transthoracic echocardiography with the speckle tracking method was used to estimate the LAS reservoir (LASr) and direct measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In accordance with the above, in their recent article, Uziębło-Życzkowska et al [6] found a close correlation between LAP, measured during atrial fibrillation ablation, and LA reservoir strain. The authors enrolled 172 patients with atrial fibrillation undergoing ablation and divided them according to the LA strain reservoir value into three terciles; then they compared patients with lower values (first tercile) with those with higher values (third tercile) and found that the former were older and more often women, they had a larger LA and showed a more impaired LV diastolic function.…”
supporting
confidence: 67%
“…In accordance with the above, in their recent article, Uziębło-Życzkowska et al [6] found a close correlation between LAP, measured during atrial fibrillation ablation, and LA reservoir strain. The authors enrolled 172 patients with atrial fibrillation undergoing ablation and divided them according to the LA strain reservoir value into three terciles; then they compared patients with lower values (first tercile) with those with higher values (third tercile) and found that the former were older and more often women, they had a larger LA and showed a more impaired LV diastolic function.…”
supporting
confidence: 67%
“…There are reports that E′ value and E/e′ ratio, were also associated with decreased LAAV and can be useful parameters for the prediction of LAA blood stasis in patients with nonvalvular AF 24 , 25 . In addition, LASr, which has shown significant added value in many cardiac diseases 34 , was previously found to correlate negatively with left atrial pressures in AF patients with sinus rhythms during echocardiography 35 . It is currently being used increasingly in clinical practice, particularly in patients with AF and HFpEF.…”
Section: Discussionmentioning
confidence: 97%
“…Low LASr value were associated with higher LAP in AF with sinus rhythm. The cut‐off value of LASr predicting high elevated LAP was 21.88% (AUC .81) for the patients with sinus rhythm in AF, while 11.25% (AUC .66) for the AF group 13 . Muka et al.…”
Section: Discussionmentioning
confidence: 98%